Religiosity and Telomere Length: Moderating Effect of Religiosity on the Relationship Between High-Risk Polymorphisms of the Apolipoprotein E and TOMM40 Gene and Telomere Length. (June 2020) - Wang, Liqun; Koenig, Harold G.; He, Zhiqiang; Sun, Xiaoya; Shohaib, Saad Al; Wang, Zhizhong
Objective: The current study seeks to examine the relationship between religiosity and telomere length (TL) in an older Chinese Muslim sample and to explore the moderating effect of religiosity on the relationship between high-risk polymorphisms and TL.Methods: A cross-sectional study of 1, 692 community-dwelling adults aged 55 or older was conducted. Apolipoprotein E and TOMM40 (rs2075650) gene polymorphisms and TL were determined using standard procedures. Ordinal logistic regression was used to examine the associations.Results: Religiosity was significantly and positively related to TL. A significant interaction emerged between religiosity and the rs2075650 G polymorphism in predicting TL. Stratified multivariate analyses demonstrated that the relationship between the rs2075650 G state and TL was particularly strong among those who were more religious, as hypothesized.Conclusion: The findings revealed that religiosity may influence cellular aging in part by modifying the effect that high-risk genes have on increasing vulnerability to dementia and cognitive impairment.